TFETF Framework Development in MOOC Based on Art-Technopreneurial - Iraji; Abdul Rahman Prasetyo; Ike Ratnawati; Alby Aruna; Adinda Marcelliantika; Eka Putri Surya; Ginanjar Atma Wijaya (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study explores family economic empowerment through the Framework Economy of the Family (TFETF) through the implementation of the Massive Open Online Course (MOOC) through concrete-based pottery, supporting the development of creative family technopreneurs. Integrating traditional arts, entrepreneurship education and technology is the key to creating innovative human resources in the digital era. This research uses the ADDIE model to design a MOOC curriculum that facilitates collaboration in entrepreneurship and craft technology. The results of the research in the form of developing the TFETF framework obtained a media expert validation score of 91.45%, material expert validation 90%, practicality test 90%. The TFETF framework developed has proven effective in strengthening the family economy by providing adaptive learning materials, helping overcome geographic and socio-economic barriers and encouraging social inclusion and global connectivity.